1970
DOI: 10.1172/jci106424
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside deaminase: an enzymatic marker for stress erythropoiesis in the mouse

Abstract: A B S T R A C T The level of nucleoside deaminase was determined in extracts of mouse tissues obtained during a period of accelerated erythropoiesis induced by hypoxia, hemorrhage, or the injection of phenylhydrazine. Under these conditions a striking (10-to 100-fold) elevation of the enzyme activity occurred in the spleen. Similar results were obtained with the injection of purified erythropoietin. In control animals, only a trace of nucleoside deaminase activity was detected in the blood. During the reticulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…aminase increased during Me2SO-stimulated differentiation while the activity of the purine biosynthetic enzymes decreased. This elevation in cytidine deaminase activity also occurs during accelerated erythropoiesis in mice and is thought to accompany the development of erythroid cells in vivo (14). The present observation that the specific activity of the PRibN-synthesizing enzymes was repressed in differentiating cells in vitro stresses the importance of these enzymes in the regulation of de novo purine biosynthesis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…aminase increased during Me2SO-stimulated differentiation while the activity of the purine biosynthetic enzymes decreased. This elevation in cytidine deaminase activity also occurs during accelerated erythropoiesis in mice and is thought to accompany the development of erythroid cells in vivo (14). The present observation that the specific activity of the PRibN-synthesizing enzymes was repressed in differentiating cells in vitro stresses the importance of these enzymes in the regulation of de novo purine biosynthesis.…”
Section: Discussionsupporting
confidence: 54%
“…Our earlier studies had shown that, unlike mature erythrocytes, the immature cells in spleens of virus-infected leukemic mice have the enzyme systems required for de novo synthesis of purines and that the activity of the purine biosynthetic enzymes increased in a characteristic pattern during the course of the disease. Similarly, the activity of cytidine deaminase, an enzyme important in pyrimidine metabolism, was comparable in erythroleukemic cells in culture and in the cells of leukemic spleens (9,14).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There were no human red cells circulating long term after transplantation, after human red cell infusion, or after splenectomy. The lack of human red cell output may result from one or more of several possibilities: differences in the erythroid stress response (24), low globin gene and protein expression (15,28), lack of human-specific cytokines (19), species differences between human and murine transferrin, or other anti-human inhibitory signals.…”
Section: Introductionmentioning
confidence: 99%
“…5 Alternatively, it was suggested that increased HbF results primarily from accelerated differentiation of developmentally immature erythroblasts that were thought to normally express high levels of gamma-globin. 6 Mechanistic studies of growth-or signaling-related modulation of human fetal hemoglobin are currently not possible in murine models due to well-described differences in the erythroid stress response 7 as well as the inability to detect globin gene or protein expression in the circulating blood of nonobese diabetic-severe combined immunodeficiency (NOD/SCID) mice that received transplants of human bone marrow. 8 For these reasons, cultures of primary human erythroblasts are the method of choice for defining relationships between erythroid growth, differentiation, and HbF.…”
Section: Introductionmentioning
confidence: 99%